2009
DOI: 10.1517/14740330903173217
|View full text |Cite
|
Sign up to set email alerts
|

Prognostication of pancreatic adenocarcinoma by expression of thymidine phosphorylase/dihydropyrimidine dehydrogenase ratio and its correlation with survival

Abstract: We found a survival benefit of approximately 4 months in our study correlating with lower TP/DPD ratio and this is quite significant in a disease whose > 5-year survival is < 5%. The TP/DPD ratio may be used as an independent marker for prognostication for LAPC and it may help in determining the chemotherapy duration, choices and possibly toxicities as well. Larger studies are needed to study the relation ship between TP/DPD ratio with these efficacy parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…It important to note that no survival difference was found between TP positive and TP negative patients who had not received chemotherapy. There are other papers that have shown that TP/DPD ratio is a predictive biomarker for capecitabine in head and neck cancer [66] and pancreatic adenocarcinoma [67]. In contrast to these findings, a phase II trial found no association between TP/DPD ratio and the efficacy of concomitant chemoradiation with capecitabine in patients with pancreatic adenocarcinoma [68].…”
Section: Tp As a Predictive Biomarkermentioning
confidence: 88%
“…It important to note that no survival difference was found between TP positive and TP negative patients who had not received chemotherapy. There are other papers that have shown that TP/DPD ratio is a predictive biomarker for capecitabine in head and neck cancer [66] and pancreatic adenocarcinoma [67]. In contrast to these findings, a phase II trial found no association between TP/DPD ratio and the efficacy of concomitant chemoradiation with capecitabine in patients with pancreatic adenocarcinoma [68].…”
Section: Tp As a Predictive Biomarkermentioning
confidence: 88%
“…With regards to cardiotoxicity, it has been long recognized than 5FU causes cardiac toxicity 60 . However, the syndrome of 5FU -associated cardiotoxicity remains poorly defined and its incidence may be underestimated.…”
Section: Tolerabilitymentioning
confidence: 99%
“…However, the syndrome of 5FU -associated cardiotoxicity remains poorly defined and its incidence may be underestimated. Large series suggest that clinically demonstrated 5FU-related cardiotoxicity ranges from 1.6 to 4% 60 .…”
Section: Tolerabilitymentioning
confidence: 99%
“…TP/DPD ratio seems to correlate positively with the efficacy of capecitabine in human xenograft models. Saif et al demonstrated in a study that a lower TP/DPD was associated with a survival benefit of 4 months [ 57 ]. This looks small, but we must take into account that the 5-year survival is less than 5%.…”
Section: Genetic Factors Affecting Outcomementioning
confidence: 99%